The international strategies of universities: deliberate or emergent?. Issue 8 (3rd August 2019) - Soliman, Samar; Anchor, John; Taylor, David
ABSTRACT: The internationalisation of higher education, which has developed from a number of separate initiatives to become a strategic objective in its own right, has not been investigated from a strategic organisational perspective. Case studies of four English universities were developed via a Grounded Theory methodology. Mintzberg and Waters' [1985. "Of Strategies, Deliberate and Emergent." Strategic Management Journal 6 (3): 257–272] 'deliberate' and 'emergent' strategies were used to analyse the trajectories of the international strategies of the case study universities. It was found that the international strategies were deliberate in each strategic period, whereas they were emergent over a longer time frame. Internationalisation has gone through three phases, as the approaches of universities to this phenomenon have matured and progressed from operational to strategic. A conceptual model which describes the trajectory of the international strategies of these English universities is developed and is a major addition to the internationalisation literature. Future research should examine the applicability of the model to other countries.